WMI2: interactive mathematics on the web - Kovács, Zoltán (Teaching Mathematics and Computer Science, 2007)
After 5 years of experiments and feedback we decided to continue the software development on WebMathematics Interactive, a web-based e-learning tool, rewriting it from scratch. The demonstration version of WebMathematics Interactive 2 (WMI2) has been shown to the expert audience on the CADGME conference. In this article we summarize the development goals and results.